2020
DOI: 10.15294/biosaintifika.v12i1.22548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Induced Polyploidy on Plant Growth, Chlorophyll and Flavonoid Content of Artemisia cina

Abstract: Artemisia cina is one of a member of genus Artemisia that has potential as a medicinal plant. However, the levels of Artemisia medicinal bioactive compounds are very low. Polyploidization is an alternative method that can enhance of growth and secondary metabolite productions of plants. The aims of this research were to determine the effect of polyploid induction using colchicine and plant growth regulator toward plant growth, the chlorophyll, kaemferol and quercetin contents of A. cina. Four different A. cina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Fredes et al, (2016) and Levi et al, (2014), reported that the use of tetraploid (allo and auto) watermelon rootstocks with a strong root system can provide high graft compatibility and a high survival rate, while the increased chlorophyll content and high antioxidant activities of tetraploid watermelon rootstocks can promote plant growth and stress tolerance without negatively af- leaf width, compared to diploid orchids (Chung, Kuo, & Wu, 2017). Polyploid plants showed higher leaf and root growth compared to diploid plants in Artemisia cina (Kasmiyati, Kristiani, & Herawati, 2020), Kim et al, (2004), reported that the number of adventitious roots in polyploid ginseng plants is higher than in diploid plants.…”
Section: Resultsmentioning
confidence: 99%
“…Fredes et al, (2016) and Levi et al, (2014), reported that the use of tetraploid (allo and auto) watermelon rootstocks with a strong root system can provide high graft compatibility and a high survival rate, while the increased chlorophyll content and high antioxidant activities of tetraploid watermelon rootstocks can promote plant growth and stress tolerance without negatively af- leaf width, compared to diploid orchids (Chung, Kuo, & Wu, 2017). Polyploid plants showed higher leaf and root growth compared to diploid plants in Artemisia cina (Kasmiyati, Kristiani, & Herawati, 2020), Kim et al, (2004), reported that the number of adventitious roots in polyploid ginseng plants is higher than in diploid plants.…”
Section: Resultsmentioning
confidence: 99%
“…This increase in resistance was probably due to the increase of pod's flavonoid content, which produced the purple color of the pods. Kasmiyati et al (2020) reported induced polyploidy using colchicine be able to increase flavonoid content. Furthermore, flavonoid affect the behavior of aphid especially it could decrease sap ingestion activity (Goławska et al, 2014;Stec et al, 2021).…”
Section: Incidence Of Cowpea Aphid (Aphis Craccivora) On Cowpea Podsmentioning
confidence: 99%
“…Improvements in secondary biometabolites productions could be due to morphological, physiological as well as genetic manifestations engendered upon by induced autoploids. Some of such illustrative causes of autoploidy-mediated secondary metabolite augmentation are increase in stomatal sizes and densities leading to increased photosynthates output [ 67 ], heterosis and gene redundancy imparting transgressive meliorism [ 56 , 66 , 68 ]. Shmeit et al [ 62 ] reckoned that improvised primary metabolism could be the presumptive cause of ameliorated secondary metabolism.…”
Section: Main Textmentioning
confidence: 99%
“… Seed Colchicine; 0.2%; 24 h Diploid➔tetraploid (2n=4x=44) Increase in rebaudioside-A content (2.84%) [ 67 ] Artemisia cina Soaked in colchicine soln. Shoot Colchicine; 100 mg/l Diploid➔ tetraploid (2n=4x=36) Increase in quercetin content (1.34-fold); kaempferol content (1.47-fold) [ 68 ] Artemisia cina NM NM Colchicine; NM; NM Diploid➔ tetraploid (2n=4x=36) Increase in artemisinin content (NM) [ 69 ] Solanum tuberosum In vitro colchicine treatment ( Solanum tuberosum × Solanum kurtzianum ) Colchicine; NM; NM Diploid➔tetraploid (2n=4x=48) (Allotetraploid) Increase in sesquiterpenes (22-fold) [ 70 ] Oryzalin treatment Diploid line ( Solanum kurtzianum ) Oryzalin; NM; NM Diploid➔tetraploid (2n=4x=48) (Autotetraploid) Increase in sesquiterpenes (6-fold) 2 - IP 2-isopentenyl adenine; B5 Gamborg’s B5 media [ 71 ]; BA N 6 -benzyladenine; d days, DMSO dimethyl sulfoxide; LI light intensity; M1 media [woody basal salt mixture (2.3 g/l) + Murashige and Skoog modified vitamins (1000x) (1 ml/l) + Sucrose (25 g/l) + 2IP (3 μM) + Agar (7 g/l)]; m months; min minutes; MS Murashige and Skoog [ 72 ]; MSL MS Liquid Media; NAA α-naphthalene acetic acid; NM not mentioned; PP photoperiod; rpm rotation per minute; r . t .…”
Section: Introductionmentioning
confidence: 99%